The Influence of Tax Literacy on Tax Compliance With Tax Sanctions as A Moderating Variable - Tri Widyastuti Ningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is quantitative research with an exploratory approach. The data used in this research is primary data that researchers obtained from various sources from all over, starting from journals, books, scientific articles, and other things that are usually used in every scientific research. The data used is primary data obtained directly through distributing questionnaires as an instrument. This data was collected and then analyzed using the smart PLS 4.0 analysis tool. The result in this article show the Tax Literacy variable can have a positive relationship and a significant influence on Tax Compliance because the P-Values ​​value is positive and is below the 0.05 significance level, namely 0.002. These results indicate that a good understanding of increasing Tax Literacy can make people aware of the importance of taxes, their benefits for the general public, themselves as individuals, and other things. In line with the explanation above, in row d below, the third table of Path Coefficients above also shows similar results if the Tax Sanctions variable can strengthen the influence of the Tax Literacy variable on Tax Compliance because the direction of the P-Vlues value is positive and is below the 0.05 significance level, namely 0,000